Expression of SCGB1C1 gene as a potential marker of susceptibility to upper respiratory tract infections in elite athletes – a pilot study - Orysiak, J; Malczewska-Lenczowska, J; Bik-Multanowski, M (Biology of Sport, 2016)
High levels of exercise in athletes result in temporary immunosuppression, which could increase the susceptibility to upper respiratory tract infections. Understanding of immunological mechanisms responsible for this phenomenon could enable optimization of training schemes for elite athletes and avoidance of infection-related episodes of absence during sports championships. The aim of this study was to detect genes that may be responsible for modulation of individual susceptibility to infections. The blood and saliva samples were collected from 10 healthy, medically examined kayakers (4 females and 6 males) aged 24.7 ± 2.3 years. All samples were taken in the morning, after overnight fasting, in a seated position. The ELISA method was used to determine the levels of secretory immunoglobulin A (sIgA) and interleukin 5 (IL-5). Whole genome expression in blood was assessed using microarrays. The study did not reveal any significant correlation between genome expression and sIgA concentration. However, low expression of a gene involved in protection against the common cold – secretoglobin 1C1 (SCGB1C1) – was detected in athletes with high IL-5 concentrations (corrected p=0.00065; fold change=3.17). Our results suggest that blood expression of the SCGB1C1 gene might be a marker of susceptibility to upper respiratory tract infections in athletes.